2018
DOI: 10.1177/0043820018776410
|View full text |Cite
|
Sign up to set email alerts
|

Global Governance, Tax Treaties, and Credible Commitments

Abstract: The international tax regime appears to be a weak system of global governance on the surface; however, I find that this system remains effective. This governance structure is built upon the thousands of tax treaties that function as policy instruments for advancing the implementation of global tax policy. Yet there is conflicting evidence in relation to the efficacy of these treaties, necessitating further exploration. In this article, I offer an accessible introduction to some of the key dynamics of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 112 publications
0
1
0
1
Order By: Relevance
“…Additionally, the potential for intensified tax competition due to coordinated cross-border loss compensation further underscores the complexities in reaching international consensus on tax regulations (Haufler & Mardan, 2014;Adaga et al, 2024). Moreover, the role of tax treaties in spurring cross-border investment in securities has been highlighted as a factor in global governance and credible commitments (Johnson, 2018). Case studies of successful international tax cooperation initiatives can be observed in the context of reducing evasion by judiciously lowering tariffs and enforcing the law at the border (Tadesse, 2022).…”
Section: International Cooperation and Coordinationmentioning
confidence: 99%
“…Additionally, the potential for intensified tax competition due to coordinated cross-border loss compensation further underscores the complexities in reaching international consensus on tax regulations (Haufler & Mardan, 2014;Adaga et al, 2024). Moreover, the role of tax treaties in spurring cross-border investment in securities has been highlighted as a factor in global governance and credible commitments (Johnson, 2018). Case studies of successful international tax cooperation initiatives can be observed in the context of reducing evasion by judiciously lowering tariffs and enforcing the law at the border (Tadesse, 2022).…”
Section: International Cooperation and Coordinationmentioning
confidence: 99%
“…Additionally, the potential for intensified tax competition due to coordinated cross-border loss compensation further underscores the complexities in reaching international consensus on tax regulations (Haufler & Mardan, 2014;Adaga et al, 2024). Moreover, the role of tax treaties in spurring cross-border investment in securities has been highlighted as a factor in global governance and credible commitments (Johnson, 2018). Case studies of successful international tax cooperation initiatives can be observed in the context of reducing evasion by judiciously lowering tariffs and enforcing the law at the border (Tadesse, 2022).…”
Section: International Cooperation and Coordinationmentioning
confidence: 99%
“…This complexity is further compounded by the unintended consequences of bilateralism, such as treaty shopping and the intricate nature of the international tax system composed of thousands of bilateral tax treaties (Arel-Bundock, 2018). Tax treaties, promulgated by international organizations, serve the purpose of systematically dividing cross-border taxable base between countries to eliminate market distortions from inharmonious domestic tax policies (Johnson, 2018). Disputes over tax jurisdiction and allocation of taxing rights are common in the context of multinational corporations and international tax treaties.…”
Section: Complexity Of International Tax Treaties and Agreementsmentioning
confidence: 99%

Cross-Border Tax Challenges and Solutions in Global Finance

Joy Ojonoka Atadoga,
Joseph Kuba Nembe,
Noluthando Zamanjomane Mhlongo
et al. 2024
Financ. account. res. j.